KEMAMPUAN BERPIKIR ANALISIS DALAM MENYELESAIKAN SOAL FISIKA PESERTA DIDIK SMAN SE-KOTA MAKASSAR - Lewikinta, Yustin; Martawijaya, Muhammad Agus; Hasyim, Mutahharah (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2024)
This research is quantitative descriptive research which aims to find out a picture. ability. think. analysis of high school students throughout the city Makassar. This research aims to determine analytical thinking skills in four schools, namely SMAN 4 Makassar, SMAN 6 Makassar, SMAN 9 Makassar, SMAN 23 Makassar using test instruments in the form of essay questions using a descriptive quantitative approach with a total research sample of 183 students, namely 62 participants. educated from SMAN 4 Makassar. 53 students from SMAN 6 Makassar, 22 students from SMAN 9 Makassar, and 46 students from SMAN 23 Makassar. The research instrument used is a test with 12 valid questions out of 22 questions that have been validated by experts, where the first indicator consists of 5 items, the second indicator consists of 4 questions and the third indicator consists of 3 questions. Test questions. This is used for collecting quantitative research data because it is a test instrument. to measure a person's abilities in a particular field. Instruments that. used to collect data in the form of essay tests that are developed accordingly. with indicators of analytical thinking skills which include analytical indicators. elements or elements, relationship analysis, and system analysis. And data mining through interviews was carried out using semi-structured interviews. Based on the research data, it was found that the physics analysis thinking ability of students at SMAN throughout Makassar City was in the medium category with an average amounting to 21.84. This is due to a lack of practice in analytical questions given.